Prevalence of Parasitic Infection in Sheep From different Regions in Baghdad: Shehella Rsul Fadl Dalia Ahmed Kalef soadad Mashaan Abbas - Fadl, Shehella Rsul (The Iraqi Journal of Veterinary Medicine, 2011)
This research concerns (306)faecal samples from different regions in Baghdad from sheep were examined,the results showed that 230 samples were infected with gastrointestinal parasites with total rate 75.1% which included : 49.0% of coccidiosis ( 9 species of Eimeria were recorded E.parva, E.ovina, E.crandalli s, E. weybridgensi, E. pallida, E. granulosa E .faurei, E. ovinadalis E.marsica) , 21.2% Nematodes 7.84% ,6.5% ,4.5%, 2.2% for Haemonchus, Trichostrongylus ,Nematodiru,and Trichuris in respectively , while the percentage of trematodes & cestodes infections were 4.9% for fasciola 2.28% , Paramphistomum 1.6% , Moniezia 0.9% .Age factor influenced on infection percentage it is higher in younger with coccidiosis infection 25.4% while it is higher in aged animals with nematodes% 10.13 & 1.96% for trematodes & cestodes. Prevalence of coccidiosis infection showed seasonal diversity it is higher in winter, while the rate of infection with nematodes & trematodes is higher in summer & lowers in winter.